Promoting youth employment during COVID-19: A review of policy responses - Werner Eichhorst; Paul Marx; Ulf Rinne; Johannes Brunner (Institute of Labor Economics (IZA), 2022)
Economic and social disruptions caused by the COVID-19 crisis have particularly affected younger people, and therefore policy should respond with measures, programmes and initiatives targeted at this population group. Next to broader labour market and economic measures, which ultimately also benefit younger people, youth-targeted measures are needed given the specific impacts of the pandemic and resulting challenges. Against this background, this policy brief gives an overview on actual policy responses in the area of youth employment during the COVID-19 crisis in 20 selected countries. If such measures are implemented, they share the common goals of reducing the negative impacts of the COVID-19 crisis on younger workers and avoiding long-term scarring effects. However, the precise nature, extent and scope of such measures substantially differ across countries. Given the fragility and large uncertainty of economic recovery that is still present in early 2022, broader policy support continues to be needed, including specific policy measures targeting youth.
Keywords: E24; H12; J08; J13; J68; O57; 330; work; decent work; employment policy; education; skills; rapid assessment; economic recovery; economic sectors; gender equality; youth; COVID-19; survey